2020
DOI: 10.1590/2177-6709.25.2.052-060.oar
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of antibacterial effects of orthodontic composites containing different nanoparticles on Streptococcus mutans at different times

Abstract: Introduction: Plaque accumulation can cause white spot lesions. Adding nanoparticles to composites can be effective in reducing the number and function of microorganisms. Objective: The aim of this study was to evaluate the antibacterial effects of orthodontic composites containing different nanoparticles on Streptococcus mutans at different times. Methods: Hydroxyapatite, titanium oxides, zinc oxide, copper oxide and silver oxide nanoparticles were prepared at 0.5% and 1% weight concentrations. Accordingl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 26 publications
1
41
0
3
Order By: Relevance
“…We used 0.3% weight concentrations of AgNPs and measured the diameter of growth inhibition at 24 h and 30 days observing significant antibacterial effect at both time points. Previous studies confirmed that orthodontic adhesive with AgNPs were effective against Streptococcus mutans [ 34 , 35 ]; however, some did not report the same effect after 30 days. For 0.5% and 1% weight concentrations [ 34 ], although there was difference in the diameter of growth inhibition at 24 h, the same effect was not observed at 30 days.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…We used 0.3% weight concentrations of AgNPs and measured the diameter of growth inhibition at 24 h and 30 days observing significant antibacterial effect at both time points. Previous studies confirmed that orthodontic adhesive with AgNPs were effective against Streptococcus mutans [ 34 , 35 ]; however, some did not report the same effect after 30 days. For 0.5% and 1% weight concentrations [ 34 ], although there was difference in the diameter of growth inhibition at 24 h, the same effect was not observed at 30 days.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies confirmed that orthodontic adhesive with AgNPs were effective against Streptococcus mutans [ 34 , 35 ]; however, some did not report the same effect after 30 days. For 0.5% and 1% weight concentrations [ 34 ], although there was difference in the diameter of growth inhibition at 24 h, the same effect was not observed at 30 days. Therefore, authors suggested a short-term antibacterial effect for AgNPs [ 34 ].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Yassei et al [50] used copper oxide nanoparticles to create antibacterial properties in dental composites. Although this compound had an antibacterial effect in the composites, it reduced the depth of cure but used the 3,4-dihydropyrimidin-2 (1H) -ones did not show a significant difference in depth of cure.…”
Section: Discussionmentioning
confidence: 99%
“…It was proved by Yassaei et al [ 70 ], that no significant difference was found between silver and copper oxide (CuO) nanoparticles, but it was noted that a curing time increased with the use of copper material when compared to the silver one. The former is cheaper and additionally both physically and chemically more stable than the latter.…”
Section: Nanomaterials In Orthodonticsmentioning
confidence: 99%